Pengaruh Inovasi Produk pada Kinerja Keuangan dengan Adopsi Teknologi di Perusahaan XYZ di Indonesia - Sono, Mohammad Gifari; Sudiana, Urip; Said, Saida; Utami, Eva Yuniarti; Hartati, Hartati (Eastasouth Institute, 2024)
The paper focuses on the impact of product innovation on financial performance. Adoption of technology plays a crucial role in driving product innovation. Measurement of product innovation is done using Likert scale with four indikators. Measurement of technology adoption is done using Likert scale with five indikators. Financial performance is measured using liquidity, solvency, profitability, and activity ratios. The study examines the impact of product innovation on financial performance. Adoption of technology and innovation in products can improve financial performance. The findings provide a basis for companies to focus on innovation and technology adoption. Practical implications include expanding innovation initiatives and investing in human resources. The study has limitations in terms of specific company context and aspects studied.